Quasi-normal modes and stability of Einstein–Born–Infeld black holes in de Sitter space - Chong Oh Lee (European Physical Journal C: Particles and Fields, 2020)
Abstract We study gravitational perturbations of electrically charged black holes in (3+1)-dimensional Einstein–Born–Infeld gravity with a positive cosmological constant. For the axial perturbations, we obtain a set of decoupled Schrödinger-type equations, whose formal expressions, in terms of metric functions, are the same as those without cosmological constant, corresponding to the Regge–Wheeler equation in the proper limit. We compute the quasi-normal modes (QNMs) of the decoupled perturbations using the Schutz–Iyer–Will’s WKB method. We discuss the stability of the charged black holes by investigating the dependence of quasi-normal frequencies on the parameters of the theory, correcting some errors in the literature. It is found that all the axial perturbations are stable for the cases where the WKB method applies. There are cases where the conventional WKB method does not apply, like the three-turning-points problem, so that a more generalized formalism is necessary for studying their QNMs and stabilities. We find that, for the degenerate horizons with the “point-like” horizons at the origin, the QNMs are quite long-lived, close to the quasi-resonance modes, in addition to the “frozen” QNMs for the Nariai-type horizons and the usual (short-lived) QNMs for the extremal black hole horizons. This is a genuine effect of the branch which does not have the general relativity limit. We also study the exact solution near the (charged) Nariai limit and find good agreements even far beyond the limit for the imaginary frequency parts.